Analysis of the Effect of Corporate Social Responsibility on MSME Business Performance with Innovation as a Mediating Variable - Bimas Saputra, Ebit; Saputra, Evan (Siber International Journal of Digital Business (SIJDB), 2023)
The purpose of this study is to determine the effect of Innovation on Business Performance and to find out that Innovation mediates the relationship between Corporate Social Responsibility (CSR) and Business performance. The type of research used is quantitative research with a causal form. Data analysis used SmartPLS 3.2.6 software using the Structural Equation Model (SEM) method. The results of this study used 3 variables, namely Corporate Social Responsibility, Innovation and Performance, and the results of the analysis of the 3 variables showed that all hypotheses were significant.